Моделювання завад в задачах передачі та обробки сигналів - Соколовська, Г.В.; Щербак, Л.М.; Марценко, С.В. (Моделювання та інформаційні технології, 2011)
The article deals with the classification of interference, which operate in the
radio systems, mathematical models of noise and their characteristics in correlation
theory.